2009
DOI: 10.1111/j.1600-0404.1993.tb04212.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased generation of superoxide radicals in the blood of MS patients

Abstract: Increased generation of superoxide radical (O2‐) in the blood stimulated with phorbol myristate acetate (PMA) has been found in multiple sclerosis (MS) patients. All the subjects studied were non‐smokers and received the same hospital diet. In the MS group treated with prednisone superoxide radical generation was lower than in untreated patients, but was still above the level of O2‐ generation in controls. Plasma lipid peroxidation products, measured as thiobarbituric‐reactive substances, were slightly elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Similar results were obtained by Głąbiński et al [20]. They found increased generation of the superoxide radical after PMA stimulation in blood of MS patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results were obtained by Głąbiński et al [20]. They found increased generation of the superoxide radical after PMA stimulation in blood of MS patients.…”
Section: Discussionsupporting
confidence: 89%
“…They found that MS patients with acute exacerbation of the disease had significantly higher concentrations of pentane compared to either patients in remission or control subjects. Increased levels of lipid peroxidation products in cerebrospinal fluid and increased erythrocyte peroxidisability were also reported in MS patients [20].…”
Section: Discussionmentioning
confidence: 92%
“…These findings suggest that widespread disruptions in brain biochemistry may contribute to myelin and axonal damage in tissues that appear normal on gross examination. Multiple lines of evidence corroborate findings from brain imaging studies including findings of cytokine imbalance, oxidative stress, cytoskeletal damage and neurotransmitter abnormalities (Glabinski et al , 1993 ; Semra et al , 2002 ; Bartosik-Psujek and Stelmasiak, 2006 ; Skundric et al , 2006 ; Bartos et al , 2007 a , b ).…”
Section: Introductionmentioning
confidence: 53%
“…With cytokine activation, free‐radical production increases and this has been demonstrated in MS (Glabiński et al. ). NAC inhibits the toxicity of TNF and in an animal model of MS, it inhibited the development of MS‐like pathology (Lehmann et al.…”
Section: Introductionmentioning
confidence: 91%
“…There is a marked increase in expression of TNF in active multiple sclerosis (MS), and a correlation exists between cerebrospinal fluid levels of TNF and the severity and progression of disease (Sharief and Hentges 1991). With cytokine activation, free-radical production increases and this has been demonstrated in MS (Glabi nski et al 1993). NAC inhibits the toxicity of TNF and in an animal model of MS, it inhibited the development of MS-like pathology (Lehmann et al 1994).…”
Section: Multiple Sclerosismentioning
confidence: 99%